(untitled) (International Journal of Engineering and Computer Science, 2025)
The increasing demand for high data rates, massive connectivity, and low latency in next-generation wireless communication systems could not be efficiently met using conventional orthogonal multiple access (OMA) schemes. This limitation necessitated the shift toward Non-Orthogonal Multiple Access (NOMA) techniques, particularly Interleaved Division Multiple Access (IDMA), which emerged as a promising candidate for 5G and beyond due to its improved system flexibility, spectral efficiency, and enhanced coverage. Despite these advantages, IDMA faced two critical challenges: optimal interleaver design and the selection of an efficient forward error correction (FEC) scheme. In this study, the performance of an LDPC-coded IDMA system employing a Gold sequence interleaver was analyzed under various conditions. The system’s bit error rate (BER) performance was evaluated over Rayleigh fading and additive white Gaussian noise (AWGN) channels with different interleaving schemes and FEC techniques. The BER versus Eb/No (energy-per-bit-to-noise-power spectral density ratio) analysis revealed that the CDMA system exhibited a BER of 0.0026101, whereas the IDMA system achieved a significantly lower BER of 0.0004015, reflecting an 18.25% improvement in error performance. Moreover, the proposed Gold sequence interleaver, when integrated with LDPC, outperformed conventional interleavers including random, convolutional, and tree interleavers by attaining the lowest BER of 0.001312500 at 9 dB. These findings demonstrated that the Gold sequence-based LDPC-IDMA system achieved near-optimal performance while maintaining low computational complexity, making it suitable for practical 5G implementations.